2018
DOI: 10.3390/geosciences8040130
|View full text |Cite
|
Sign up to set email alerts
|

A Physical Study of the Effect of Groundwater Salinity on the Compressibility of the Semarang-DemakAquitard, Java Island

Abstract: Semarang-Demak and other cities along the coast of North Java are vulnerable to land subsidence. The presence of saline groundwater in the coastal region is thought to affect the high subsidence rate, in this case the compressibility of the aquitard layer. We aimed to analyze the effects of groundwater salinity on the compression characteristics of the Semarang-Demak clay using physical analysis. Methods included the determination of groundwater salinity, clay mineralogy and fabrics, and consolidation tests un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…the variety of groundwater condition from fresh to brackish/saline as the result of depositional process. Measurement electrical conductivity in the aquifers and aquitards of the Semarang-Demak alluvial plain Sarah et al, 2018) showed the variety of groundwater quality as shown in the subsurface profiles in Figure 2a and 2b. Both figures show that the electrical conductivity of Damar Formation is low (660 μS/cm), and so is the Garang delta on top of the Damar Formation (EC of 650 -756 μS/cm).…”
Section: J O Gmentioning
confidence: 97%
See 1 more Smart Citation
“…the variety of groundwater condition from fresh to brackish/saline as the result of depositional process. Measurement electrical conductivity in the aquifers and aquitards of the Semarang-Demak alluvial plain Sarah et al, 2018) showed the variety of groundwater quality as shown in the subsurface profiles in Figure 2a and 2b. Both figures show that the electrical conductivity of Damar Formation is low (660 μS/cm), and so is the Garang delta on top of the Damar Formation (EC of 650 -756 μS/cm).…”
Section: J O Gmentioning
confidence: 97%
“…The engineering properties of the Semarang and Demak clays are influenced by the groundwater salinity, giving different compressive properties and hydraulic conductivity for freshwater and saline clays. The fresh to saline groundwater varies over depth, the material properties were applied according to its groundwater quality as had been outlined by Sarah et al (2018). The material properties used in the numerical and analytical modeling were determined from laboratory test results as summarized in Table 1.…”
Section: Model Set-upmentioning
confidence: 99%
“…The first scientists writing about land subsidence were interested in the displacement of the Semarang shoreline (erosion) and tidal flooding. Much of their analysis was based on the work of van Bemmelen, whose observations about unconsolidated sediments were – and still are – mobilized to explain the processes of sedimentation and erosion that are at the core of land subsidence in Semarang (Abidin et al, 2013; Sarah et al, 2018, 2020). Five hundred years ago, the shoreline was up to 5 km inwards from where it is now.…”
Section: Uncertainties and Politics In Land Subsidence Sciencementioning
confidence: 99%
“…A reader is likely to come across descriptions that are very similar to this one when doing a basic search engine inquiry about land subsidence. Geological definitions characterize subsidence as the ‘downward displacement of the land surface relative to certain reference surface’ (Abidin et al, 2015: 2) stemming from the ‘subsurface movement of earth materials’ (Sarah et al, 2018: 1). While the definition is relatively straightforward, the excerpt from the USGS website reveals that studying land subsidence is not easy: it is gradual, widespread, and often requires sophisticated technologies.…”
Section: Introductionmentioning
confidence: 99%
“…The problems are varied, interrelated, and complex [10]. Land subsidence, for example, in combination with other coastal-area threats, such as sea-level rise, storm surge, coastal erosion, damage caused by mangrove ecosystems, and being upstream of a river, has multiplied the risks of the coastal areas [9][10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%